The European Union illuminated : its nature, importance and future - El-Agraa, Ali M.; SpringerLink (Online service) (London : Palgrave Macmillan UK, 2015)
The European Union Illuminated: Its Nature, Importance and Future is addressed to the average educated person. This is because the EU is under great stress due to misconceptions held by the general public, propagated by certain EU political parties, especially by the UK's Conservative Party and UKIP.
Keywords: World politics; Macroeconomics; International economics; Economic policy; Economic history